Readability and Visuals in Medical Research Information Forms for Children and Adolescents. (February 2015) - Grootens-Wiegers, Petronella; De Vries, Martine C.; Vossen, Tessa E.; Van den Broek, Jos M.
Children are often-overlooked receivers of medical information, and little research addresses their information needs. However, young children are capable of understanding medical concepts, and they express the desire to be informed. This study addresses the quality of medical research information forms for children in the Netherlands, by assessing text readability and the role of visuals. Children's reading books, nonfiction books, and textbooks were used as comparison. Seven focus groups were conducted to identify children's preferences and needs for text and supporting visuals. We argue that the use of visuals is a powerful, but neglected, tool to improve medical information for minors.